Perceptions of low-middle income Filipinos on interior design - Punzalan, Jelly T.; Queveo, Ma. Teresa P. (2007)
This study aims to determine the different perceptions of low-middle income Filipinos on interior design and the implications of such perceptions on the image and identity of the profession. It will also establish the truthfulness of such perceptions based on theoretical knowledge. The study promotes awareness within the interior design community and the society regarding interior design and its extent of availability and applicability to the lifestyle of Filipinos from the low-middle income class. By providing information on how people from this income bracket perceive and understand interior design, the study brings up issues regarding interior design which have implications on the field and might require resolutions. A survey was conducted through the use of questionnaires and follow-up interviews for vague responses. Using quota sampling, 120 respondents from Brgy. Culiat, Quezon City were selected to participate in this study, seventy-five of which are female and the remaining forty-five were male. From the survey, there emerged four major perceptions regarding interior design. First, the respondents believed that interior design is important. Second, the tasks of an interior designer, a decorator, and an architect were perceived to be interchangeable. Third, most of the respondents preferred female interior designers. And last, interior design is for those who have sufficient budget for it. From these findings, the interior design community must take measures to address the identified issues in this study. The different perceptions of the respondents on interior design, either wrong or right, should serve as a cue that the profession still needs to establish itself the way it wants it to be.
Thesis (BID)--University of the Philippines Diliman.
Keywords: Interior decoration -- Psychological aspects